Performance optimization of electret air filter. (26th September 2022) - Li, Xiaohui; Ma, Xingchen; Chang, Li; Liu, Jianqing; Liao, Julong; Zhang, Xiaoqing
Abstract: With the rapid development of the society, the severe haze weather caused by particulate matters (PMs) occurs frequently. Electret air filters have been playing an important role in purifying the air and alleviating the pollution. In this work, electret air filters were fabricated based on the polypropylene (PP) materials to investigate their filtering performance to the PMs. First, the electret performance of the PP-based films was mainly focused on. The charge storage stability of the electret films was found to be associated with the material recipe and the electret technique. Introducing 1% of tourmaline into the isotactic PP can realize the best charge storage stability, while adding the graphene can weaken the charge stability. And the electret techniques including the high-temperature pre-aging and polarization at elevated temperature were adopted to optimize the charge storage performance. Then, based on the optimized electret materials and electret technique, the purification performance of the electret filter elements dependent on the polarization condition was evaluated. The present work can provide an optimization strategy to improve the performance of electret materials and electret air filters.